Seismological reference earth model in South China (SREM-SC): Crust and uppermost mantle - Hu, Jiamin; Sun, Weijia; Liu, Congcong; Tang, Qingya; Fu, Li-Yun (Frontiers in Earth Science, 2023)
The South China Block is located on the eastern margin of the Eurasian Plate and the western margin of the Pacific Plate. The South China Block is currently in a tectonically compressed environment, while the Tibetan Plateau is moving eastward and the Philippine Sea Plate is moving westward from geodetic observations. The South China Block is an ideal place to revisit tectonic history from the Archean to Cenozoic, where its information could be well preserved in the crust. In this study, we aim to build the crustal and uppermost mantle component of the Seismological Reference Earth Model in South China (SREM-SC) to provide a background velocity model for geological interpretations and fine-scale velocity inversion. The S-wave velocity model comes from combining models inverted by ambient noise tomography and surface wave tomography. The P-wave velocity and density models are inferred from empirical relationships with S-wave velocity. The Moho depth is obtained by a weighted averaging scheme of previously published receiver function results. The P-wave and S-wave velocity models have a grid interval of 0.5°in both latitude and longitude, and with a vertical sampling interval of 5 km down to the 60 km depth. This work provides the 3-D crust and uppermost mantle structures and their tectonic implications beneath South China.